Особливості перербігу вагітності і пологів у жінок із дифузним токсичним зобом - Паєнок, О. С. (Clinical Endocrinology and Endocrine Surgery, 2010)
The specific features of the clinical course of pregnancy were studied in 46 females with diffuse toxic goiter. It was set that pregnancy at a diffuse toxic goiter is complicated by high-frequency of threat of breaking to pregnancy, placental insufficiency, by high-frequency of anomalies of childbirth. The presence of diffuse toxic goiter for pregnant predetermines high-frequency of early toxicosis (52,2%) and threat of abortion (47,8%). High-frequency of threat of breaking to pregnancy for women at a diffuse toxic goiter predetermines anomalous localization of placenta. Basic condition of successful delivery for women with a diffuse toxic goiter is achievement of the stable euthytoid state.